2009
DOI: 10.1002/ejoc.200801211
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Selectivity for Cycloadditions of Nitrones and Alkenes Tethered by Benzimidazoles: Combining Experiment and Theory

Abstract: Herein we describe a combined experimental/theoretical study on the effects of substituents on regio- and stereoselectivity in intramolecular 1,3-dipolar cycloadditions of nitrones and alkenes tethered by benzimidazoles. By employing a large substituent at position R2 or R3, complete selectivity was achieved for either the fused or bridged cycloadduct, respectively. In addition, these cycloadducts were formed as single diastereomers in all of the cycloadditions examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…S4. † It should be mentioned here that in recent times E-Z isomerization studies 64,65 on different types of nitrones have been extensively reported at the DFT level of calculations.…”
Section: Optimized Transition States On the Excited State And Ground ...mentioning
confidence: 99%
“…S4. † It should be mentioned here that in recent times E-Z isomerization studies 64,65 on different types of nitrones have been extensively reported at the DFT level of calculations.…”
Section: Optimized Transition States On the Excited State And Ground ...mentioning
confidence: 99%
“…Kurth, Tantillo and co‐workers undertook a combined experimental/theoretical study on tethered nitrone/alkene cycloaddition reactions, with the goal of controlling regioselectivity and thereby allowing access to molecular frameworks with significantly different shapes (Scheme ) 14. Quantum chemical calculations were used to rationalize initial experimental results, which led to subsequent computational predictions on systems that might have improved regioselectivity.…”
Section: Optimizing Selectivitymentioning
confidence: 99%
“…Tantillo, Kurth and co-workers performed a combined experimental/theoretical study on the effects of substituents on regio-and stereoselectivity in intramolecular 1,3-dipolar cycloadditions of nitrones and alkenes tethered by benzimidazoles (Scheme 18). 24 B3LYP calculations were employed to help rationalize the regio-and stereoselectivity observed in initial experiments, and the success of this approach then led to predictions of product distributions for additional reactions, which were then tested experimentally. Overall, it was concluded that, by employing a large substituent at position R 2 or R 3 , complete selectivity can be achieved for either the fused (B) or bridged (A) cycloadduct, respectively.…”
Section: Scheme 16mentioning
confidence: 99%